PERENCANAAN PENGEMBANGAN SITUS MAKAM LA MOHANG DAENG MANGKONA DI SAMARINDA DENGAN PENEKANAN ARSITEKTUR METAFORA - Sumboro, Heru Dwi Ari (LPPM Universitas 17 Agustus 1945 Samarinda, 2021)
Samarinda City has a variety of cultures, tourist attractions and historical places, one of which is the Tomb of La Mohang Daeng Mangkona which is one of the historical places in Samarinda City which has been recognized as a National Cultural Heritage. From several survey results, it was found that the condition of the Tomb of La Mohang Daeng Mangkona itself was not widely known by the public and did not seem optimal. Planning for the Development of the Tomb of La Mohang Daeng Mangkona in Samarinda aims to preserve the historical heritage of the Tomb of La Mohang Daeng Mangkona with an emphasis on Metaphor Architecture, which is a concept where the design has the same conceptual value with its visual objects. The conservation efforts are supported by complete infrastructure such as museums, places of pilgrimage, libraries, pavilions, souvenir kiosks, food courts, parking areas and other supporting facilities. It is hoped that the planning for the development of the grave site will increase the potential for visits to the city of Samarinda which is also connected to the history of the old Sirathal Mustaqiem mosque and Kampung Tenun, which can facilitate visitors who come according to their needs.